FORMING COMMUNICATION COMPETENCIES IN EDUCATIONAL SESSIONS WITH VISUALLY IMPAIRED CHILDREN (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article examines the development of communication skills in educational activities with visually impaired children. The study aims to identify pedagogical strategies, adaptive methods, and inclusive educational tools that effectively develop verbal, nonverbal, and social communication skills among visually impaired students. The results of the research show that tactile-auditory integration methods, structured communication-based exercises, and peer-to-peer collaboration significantly increase the level of communication skills. Purposefully designed remedial-developmental activities based on the principles of Uzbek inclusive education provide significant improvements in communicative self-confidence, vocabulary, and interpersonal interaction among visually impaired students. Practical recommendations are offered for teachers and curriculum developers.